Design, analysis and implementation of a new three‐port DC‐DC converter with bidirectional capability - Tohid Jalilzadeh; Naghi Rostami; Ebrahim Babaei; Seyed Hossein Hosseini (IET Power Electronics, 2021)
Abstract The proposed converter here is a dual‐input DC‐DC converter with bidirectional power flow. One of the inputs is unidirectional, while the other is a bidirectional port for a battery. The proposed converter can combine two alternating sources with different characteristics. The demanded power of the load can be provided by each input source individually or simultaneously. What is more, the unidirectional port can charge the battery as well as power the output load. Due to the bidirectional capability, the energy returned from the output can be stored in the battery which is suitable for electric vehicle (EV) applications. Step‐up capability, the low voltage stress on semiconductors, and the smaller number of passive elements are the other advantages of the converter. Depending on the battery usage status, four different operation scenarios are defined in the proposed converter. The converter operation is described in each scenario and the mathematical analysis is presented. Based on these, the experimental prototype is conducted to verify the characteristics and feasibilities of the converter.